Az oktatási elszámoltathatósági rendszerek elmélete - Dániel Horn (Hungarian Academy of Sciences, Institute of Economics, 2011)
– Educational accountability is a timely topic in Hungary, because the law of LXXI/2006 has practically introduced educational accountability. School report cards have been published for the third time in 2011 for each school with a 6th, 8th or 10th grade. These report cards publicize information about the students' mathematical and reading literacy skills, as well as statistics about the school and about the parents. This paper summarizes the most important theoretical and empirical literature about school accountability, using American and English studies. Although this paper is a pure summary with no intention to analyze the Hungarian system, it contains several conclusions that could be of the the Hungarian policy makers' interest.
Keywords: H41; I21; I28; 330; education; accountability; incentives; Bildungsniveau; Ungarn